Coexistence of phycoerythrin and a chlorophyll a/b antenna in a marine prokaryote. - Hess, W R (1996)
Prochlorococcus marinus CCMP 1375, a ubiquitous and ecologically important marine prochlorophyte, was bound to possess functional genes coding for the alpha and beta subunits of a phycobiliprotein. The latter is similar to phycoerythrins (PE) from marine Synechococcus cyanobacteria and bind a phycourobilin-like pigment as the major chromophore. However, differences in the sequences of the alpha and beta chains compared with known PE subunits and the presence of a single bilin attachment site on the alpha subunit designate it as a novel PE type, which we propose naming PE-III. P. marinus is the sole prokaryotic organisms known so far that contains chlorophylls a and b as well as phycobilins. These data strongly suggest that the common ancestor of prochlorophytes and the Synechococcus cyanobacteria contained phycobilins. Flow cytometric data from the tropical Pacific Ocean provide evidence that deep populations of Prochlorococcus possess low amounts of a PE-like pigment, which could serve either in light harvesting or nitrogen storage or both.